Integrating Qur'anic Values and Pepali Pitu in Islamic Education Management - Auf, Muhammad Azmi; Na’imah, Na’imah; Pradipa, Rafi; Abror, Abdillah Naufal; Huda, Syariful (Pustaka Peradaban, 2025)
In the contemporary era of globalization, Islamic education faces the critical challenge of preserving its distinct identity while effectively adapting to modern demands. This study addresses this challenge by analyzing the integration of Qur'anic values within Sunan Drajat's Pepali Pitu teachings and evaluating their relevance as a local Islamic heritage for Islamic education management. Employing a descriptive qualitative approach based on library research, the study utilized primary data from Pepali Pitu quotations and Qur'anic verses, supplemented by secondary literature on Islamic education, local wisdom, and value-based management. Findings reveal that the seven moral maxims of Pepali Pitu, encompassing social, spiritual, and ethical values, are substantively aligned with Qur'anic principles. These principles are demonstrated to serve as a foundational value system for managing Islamic educational institutions, particularly in shaping leadership models grounded in spirituality, social responsibility, and managerial ethics. The study underscores that local wisdom, exemplified by Pepali Pitu, need not be abandoned amidst global shifts; instead, it offers a strategic framework for developing Islamic education systems that are both deeply rooted in identity and adaptable to contemporary challenges. This integration provides a pathway to preserving traditional roots while ensuring global relevance.